The Influence of Consciousness, Tax Penalty and the Quality of Tax Authorities Service on Tax Complience (Survey on Taxpayer of Boarding House in Lowokwaru District) - Handayani, Ucik; Laily, Nujmatul (Universitas Negeri Malang, 2017)
: This study aims to know the effect of awareness, tax penalties and quality of service tax authorities on the boarding house taxpayer compliance at Lowokwaru area. The kind of this research is kuantitatif with population is boarding house taxpayers at Lowokwaru. Based on data from the Dinas Pendapatan Daerah Kota Malang, until the end of July 2015 there were 673 boarding house. Data was collected by proportional random sampling, the number of sample is 87 boarding house taxpayers at 8 areas. The method of collecting data by distributing questionnaires and documentation. Analysis of the data using logistic regression analysis with SPSS 21 for Windows for helping. Based on the result of analysis, the conclution is awareness, tax penalties and quality of services tax authorities is not effect to the taxpayer compliance. That is because the application of rule boarding house are new for boarding house taxpayer at Lowokwaru area and Dinas Pendapatan Daerah is not give sosialiszation about the rule to the taxpayer. So the knowledge about the rule is still low and then all independence variables not effect to dependen variable. For the next researcher can find other factors that effect to the boarding house taxpayer complience.Â Keywords: awareness, tax penalties, quality of services tax authorities, taxpayer compliance.